Strategic Roles of the Department of Youth, Sports, and Tourism in Developing Culinary Tourism in Pontianak City, West Kalimantan - Erwando; Hestiantini, Adila Puspa (Kybernology : Journal of Government Studies, 2025)
This study examines the role of tourism development strategies in enhancing culinary tourism and increasing tourist visits in Pontianak City. Using a qualitative descriptive approach, the research analyzes how promotional initiatives, institutional coordination, and stakeholder collaboration contribute to tourism growth and regional economic development. The findings indicate that effective marketing strategies, supported by intersectoral cooperation and improved destination management, have contributed to a gradual increase in both domestic and international tourist arrivals. Culinary tourism emerges as a strategic sector that not only strengthens local identity but also generates economic opportunities for small and medium enterprises. However, challenges remain in ensuring sustainable management, optimizing promotional efforts, and strengthening data-based policy formulation. Overall, the study highlights the importance of integrated governance and continuous innovation in tourism promotion to achieve sustainable and inclusive tourism development